PEMERTAHANAN BAHASA BADUY SEBAGAI IDENTITAS BUDAYA - Dwiyanti, Arie; Sapriya; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One important way to maintain the cultural identity of a community is to maintain its language. In the midst of the challenges of modernization and the influence of the Indonesian language, this article discusses how the Baduy community maintains language as an important part of their local wisdom. This research conducted qualitative research involving observations and interviews with jaro and members of the Outer Baduy community. The results show that Sundanese Baduy language not only functions as a means of communication but also functions to maintain traditional values and beliefs. But the Outer Baduy community, which interacts more frequently with the outside world, is starting to become aware of external influences. Oral teaching passed down from generation to generation, customary prohibitions, and the Puun's role as custodians of tradition are strategies for maintaining the language. According to this research, language not only functions as a symbol of identity but also helps people live together in traditional communities. These findings will provide insight into efforts to preserve other languages in the area.